The Role of Water in Women and Crime: A Blue Humanities Reading of Waterscapes in Damyanti Biswas’ The Blue Bar - Anshil Freeda R.H.; N.U. Lekshmi (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Blue humanities is an interdisciplinary field that explores the relationship between water, human life, culture, history and literature. It portrays water as a symbolic element of memory, trauma, renewal or transformation. It reveals that watery spaces expose women’s insecurity and the violence rooted in society. The paper applies the theory in the analysis of The Blue Bar (2023) by Damyanti Biswas, to examine how water has a deep and symbolic connection with a female character named Tara. As a bar dancer, Tara faces a lot of pressure in her life and struggles to survive in the dangerous urban landscape of Mumbai city. She carries emotional wounds from her past caused by bitter experiences of exploitation and insecurity. However, she constantly tries to rebuild herself by finding moments of stability even in chaotic surroundings. Water helps her to heal by keeping her mind steady and offering her a brief moment of peace and focus. Thus, it becomes a source of calmness and mental clarity for Tara. Just as every coin has two sides, watery spaces also have negative aspects that are portrayed in The Blue Bar. The paper aims to highlight the role of water as a witness to crime, since the novel includes crime scenes set near coastal areas. It attempts to reveal how coastal lines and beaches possess the trace of violence in the novel.